Typology of Waterfront Settlement in The Sibolahotang Street Balige - Rizky Annisa Lestari (International Journal of Architecture and Urbanism, 2022)
Based on bathymetric measurements (Lukman 2010) the circumference of Lake Toba is 428.7 km. Toba Samosir regency coastline length is 115.8 km or 24.7% of the total length of Lake Toba’s coastline. Balige district as the capital of Toba Samosir Regency has a density level of 49023 people/km2. With a large population and the highest density level in Toba Samosir regency, residential areas spread from the center to the outskirts of the Balige district. Along with technological advances in the current era of globalization, the potential for tourism in Indonesia is growing rapidly. Residents who live on the shores of Lake Toba compete in the tourism sector by establishing various types of inns, restaurants and various recreational areas along the shores of Lake Toba. Each waterfront settlement on Sibolahotang Street has different typology from one another waterfront settlement. By observing the waterfront settlement typology, this research is carried out so that an appropriate planning and designing towards the settlement can be done in the future